MULTI LEVEL MARKETING DALAM ISLAM (ANTARA KEHALALAN DAN ETIKA BERTRANSAKSI BERDASARKAN FATWA MUI No. 75/DSN-MUI/VII/2009) - Abd. Rahman; Sukandi Sukandi; Nahei Nahei (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Multi Level Marketing (MLM) is a marketing innovation that often generates controversy. Some scholars declare that this system is permissible according to Sharia, while others highlight financial risks and ethical concerns in transactions, such as honesty, justice, and prudence. This study aims to analyze MLM practices in the context of Islamic economic law and transaction ethics, intending to provide a balanced perspective on the permissibility and ethical implications of MLM in Islam. The research employs a descriptive qualitative approach with a literature study. Data are collected from scholarly literature such as books, journals, articles, and fatwas from Islamic scholars related to MLM. Data analysis is conducted using content analysis methods, examining relevant texts about MLM. Source triangulation is used to ensure consistency and validity of the findings. MLM involves selling products through a network of distributors who earn commissions from direct sales and sales made by recruited members. Fatwa DSN MUI No. 75/DSN-MUI/VII/2009 states that MLM is permissible if the products sold are beneficial, transactions are conducted transparently without deception, commissions are based on product sales, and the recruitment system does not harm new members